Effect of Role Play Intervention on Knowledge, Attitudes, and Actions in Mosquito Nest Eradication for DHF Prevention in Tanjung Morawa Health Center, Deli Serdang - Samuel Marganda Halomoan Manalu; Deli Syaputri; Nelson Tanjung; Erba Kalto Manik (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
One of the endemic illnesses in Indonesia and other nations is dengue fever. Aedes genus mosquitoes, particularly Aedes aegypti, are the vectors of dengue fever transmission. The growth of Aedes aegypti mosquitoes is significantly influenced by the environment. The Tanjung Morawa Health Center's working environment demonstrates the existence of dengue fever-causing mosquito breeding grounds, including the buildup of trash in the shape of bottles, glasses, aqua, plastic, and discarded water holding cans. This study aims to determine the effect of the intervention of the role play method of DHF prevention efforts on increasing community knowledge, attitudes, and actions regarding the eradication of mosquito nests in the working area of the Tanjung Morawa Health Center, Deli Serdang Regency in 2024. This research is a Quasi Experiment research with Pre and Post Test design. The research was conducted in the working area of the Tanjung Morawa Health Center, Deli Serdang Regency, which was carried out in June 2024. The population in this study were all heads of families who had DHF patients in Deli Serdang Regency. Sampling used purposive sampling technique. Data collection using pretest and postest questionnaires. This health research used standing banners and mosquito nest eradication demonstrations to improve knowledge, attitudes, and actions of the community in preventing DHF. Data analysis with bivariate analysis paired sample t-test. The results showed a significant difference in knowledge, attitudes, and actions before and after the intervention with the role play method (p-value=0.001 <0.05). Keywords: Action, Attitude DHF, Knowledge, Role Play Method